Kompetensi Literasi Digital Mahasiswa Program Studi Pendidikan Ekonomi di Riau - Paijan Rambe; Salmiah Salmiah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
Digital literacy is an essential competency that students must have to face the demands of learning and the world of work in the era of digital transformation. This study aims to describe the level of digital literacy of students of the Economics Education Study Program in Riau. The research uses a quantitative approach with a descriptive method. The research subjects consisted of 93 students who were selected using the purposive sampling technique. Data collection was carried out through a Likert scale questionnaire based on five digital literacy indicators. Data analysis uses descriptive statistics by calculating the average score and percentage of respondents' achievements. The results of the study show that students' digital literacy is in the high to very high category in all indicators. Security literacy and digital ethics earned the highest scores, reflecting awareness of personal data protection and responsible use of technology. Information literacy and digital technology are also high. However, digital content creation literacy is relatively low, so it is necessary to strengthen digital-based creative learning in higher education through contextual and project-based curriculum strategies that support digital literacy competencies in creating digital content